Jenis-Jenis Lichen Di Kampus Undip Semarang - Murningsih, Murningsih; Mafazaa, Husna (Bioma : Berkala Ilmiah Biologi, 2016)
Lichen is a symbion organism which own huge positive effect over environment. Lichen is formed by a symbiosis between fungi (mikobiont) from Ascomycetes and Basidiomycetes, and alga (fikobiont) from Cyanobacteria or Chlorophyceae. Corticolous lichens lives as an epiphyte in substrate of skin branches. It grows in Diponegoro University (Undip) campus area where a lot of shaded trees can be found as the substrate. The research aimed to define the names of lichen in Undip area by using purposive random sampling. The sampling was found in four locations: 1. Eastern of green boulevard, in front of Farm Faculty; 2. Western of green boulevard, in front of Medical Plants Biology building; 3. Northern of green boulevard, next to Economic and Business Faculty; 4. Green Boulevard as a main road, in front of Engineering Faculty. The research encountered 7 families of lichen which are Graphis scripta, Â Graphis sp. (Family of Graphidaceae), Lepraria sp. (Family of Leprariaceae), Dirinaria applanata, Dirinaria picta, Dirinaria sp., (Family of Physciaceae), Caloplaca sp. (Family of Caloplacaceae), Parmelia sp., Parmelia sulcata (Family of Parmeliaceae), Lecanora sp. (Family of Lecanoraceae), Arthonia sp. (Family of Arthoniaceae). The lichens are in groups of talus types: foliose and crustose.Â Keywords: names of lichen, talus types, Undip